Designing Online Mediation: Does “Just Add Tech” Undermine Mediation’s Ownmost Aim? - David W. Johnson (Revista Direito GV)
Abstract The norms of dispute resolution began their development alongside human communication, literally thousands of years before the internet. Mediation emerged as a social system possessed of culture-specific norms and rules that express themselves to this day, in how this mediation operates as a profoundly human system of meaning. This article asks whether these thoroughly time-tested and -refined norms specific to mediation will port over, relatively intact, into virtual space. To be sure, the answer will be seen in how designers build and implement the virtual spaces and attendant automation technology. To do that optimally, however, designers first must identify, understand and respect the values, ethics and purpose embedded in these inter-generational norms.